Cardiovascular autonomic control in patients undergoing left ventricular assist device (LVAD) support and pharmacologic therapy - Nunan, D; Sandercock, G; George, R; Jakovljevic, D; Donovan, G; Bougard, R; Yacoub, M; Brodie, D; Birks, E (2013)
Objectives The objective of the study is to determine cardiac autonomic control in patients undergoing assessment for and/or LVAD therapy. Methods Heart rate variability (HRV) was measured in 17 explanted LVAD, 17 implanted LVAD and 23 NYHA III-IV classified chronic heart failure (CHF) patients and ten healthy matched controls under three conditions: supine free breathing, standing and supine controlled breathing. Five measures of HRV were assessed: mean R-R interval (mR-R), high frequency (HF) and low frequency (LF) spectral power, LF in normalised units (LFnu), and LF to HF (LF:HF) ratio. Results Repeat measures ANOVA showed significant (p < 0.05) differences in HRV between all three conditions within groups. Lower values were observed in CHF for LF(in log natural units) compared with explanted patients (- 1.4 [95% CI - 2.6 to - 0.7], p = 0.04) and controls (- 2.1 [- 3.5 to - 0.7], p = 0.001) and for LF:HF compared with implanted patients under paced breathing conditions (z = - 2.7, p = 0.007) and controls in standing (z = - 2.9, p = 0.004) and paced breathing conditions (z = - 2.3, p = 0.02). However, no significant differences were seen between explanted, implanted and control groups under any condition. Conclusions Patients implanted with an LVAD and explanted from a LVAD following myocardial recovery demonstrate a more normal dynamic response to autonomic stimuli and have a lower HRV risk profile compared to CHF patients. © 2013 Elsevier Ireland Ltd.